22 -Year Results of an Intensive Care Unit Infection Control Program in Ribeirao Preto, Brazil. (October 2020) - Fonseca, Silvia; Freitas, Maria; Lucca, Ivana; Ferez, Marcus; Lima, Luciana; Oliveira, Itana
Abstract : Background: Healthcare-associated infection (HAI) control programs have improved patient care all over the world. Our program was implemented in 1997 in a general intensive care unit (ICU) based upon surveillance of HAI with regular infection rates feedback to the ICU team and implementation of best practices such as hand hygiene (HH) and oral care for ventilated patients, optimal care, and early removal of invasive devices. Objective: To report our decreasing HAI rates in the past 22 years. Methods: Hospital Sao Francisco 20-bed ICU admits 120–140 surgical and clinical patients monthly, with 90% occupancy. The HAI infection control team implemented HAI surveillance and developed several protocols for HAI prevention. In the past 5 years, ICU personnel initiated the collection of several indicators using random direct observations of HH compliance, central venous catheter correct care, and appropriated oral care, among others. HAI definitions followed Brazilian Health Ministry HAI definitions and were expressed as infections per 1, 000 patient days (total HAI rate) and device-related infections per 1, 000 device days. Catheter-associated urinary tract infection (CAUTI), central-line–associated blood stream infection (CLABSI) and ventilator-associated pneumonia (VAP) rates are reported here. The study period spanned January 1997 to August 2019. Measurement of antibiotic utilization (ie, meropenem, vancomycin, and piperacillin-tazobactam) was calculated by dividing the of antibiotic consumed vials by the daily defined dose and patient days. Results: The total HAI, CAUTI, CLABSI, and VAP rates dropped 70%, 85%, 84%, and 87%, respectively, from 1997 to 2019 (Table 1). From 2009 to 2019, we detected decreases in hospital use of meropenem from 52 to 38, in vancomycin from 50 to 40, and in piperacillin-tazobactam from 144 to 88. Conclusions: HAI control programs can be effective in ICUs, with impressive results, but it requires time and considerable effort. Data on compliance with basic infection control measures should accompany HAI data and should be shared with the ICU team because ICU team participation is essential to keeping the program alive. Broad-spectrum antibiotics use also decreased, with potential benefits to the hospital flora. Funding: None Disclosures: None